(untitled) (Third Sector Social Economic Review, 2023)
The aim of this study is to measure the financial soundness of non-life insurance companies in Türkiye using the Z-score, and to determine there is a statistically significant difference between the financial variables of non-life insurance companies with high and low Z-scores. Using the annual data of 22 non-life insurance companies operating in Türkiye, the Z-scores for the period 2017-2021 were first calculated. Then, whether there is a statistically significant difference between the financial variables of non-life insurance companies with high and low Z-scores in the 2017-2021 period was tested using Mann Whitney U analysis. According to the results of the analysis, it has been determined that insurance leverage ratio, equity-to-technical reserves ratio, technical profitability ratio, sales profitability ratio, premium retention ratio, and receivables from main operations-to-total assets ratio differs significantly between non-life insurance companies with high and low Z-scores.